High-magnetic-performance magnetic coded disc FeCoCr material and preparation method thereof
By constructing the [B/FeCoCrMoTi]2 multi-layer film structure and optimizing annealing conditions, the problem of difficult improvement in the coercive force and residual magnetism of the FeCoCr magnetic code disk film material is solved, and the high precision and anti-electromagnetic capability of the magnetic encoder are achieved. At the same time, the microstructure uniformity of the material is maintained, meeting the needs of high-precision magnetic encoder.
Patent Information
- Application Number
- CN202411229398.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-03
AI Technical Summary
The existing FeCoCr magnetic code disk film materials are difficult to improve coercive force and residual magnetism at the same time, and ensure the uniformity of the material, affecting the accuracy of the magnetic encoder and anti-electromagnetic interference ability.
By constructing a two-period multilayer film structure of [B/FeCoCrMoTi]2, the B target and FeCoCr target were alternately sputtered by magnetron sputtering method to generate CrB2 phase, optimize the annealing conditions to enhance coercive force and remanent magnetism, and pass through the B atom Binding with Cr atoms reduces the concentration of Cr in the FeCo-rich phase and promotes amplitude modulation decomposition.
It significantly improves the coercive force and residual magnetic properties of FeCoCr films, meets the application requirements of magnetic encoders, and maintains the microstructure uniformity of the material, improves the uniformity of nanoscale microstructures, providing important for high-precision magnetic encoders. scientific support.
Smart Images

Figure CN119220942A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnetic materials, and in particular to a high magnetic performance magnetic code disk FeCoCr material and a preparation method thereof, which can achieve a coordinated improvement in the coercive force and remanence of a semi-hard magnetic alloy film. Background Art
[0002] The magnetic encoder is a non-contact position sensor that converts the rotation angle, speed and other key motion information of the detected object into digital electrical signals through the magnetoresistance effect. It is widely used in high-precision control fields such as high-end CNC machine tools. The accuracy of the magnetic encoder directly affects the processing accuracy of CNC machine tools, and the accuracy of the magnetic encoder depends on the density and uniformity of the magnetic pole signal. Compared with optical encoders, magnetic encoders have various excellent characteristics such as anti-vibration, corrosion and pollution resistance, low cost, simple structure, etc., and are increasingly used.
[0003] The core of magnetic encoding devices is the magnetic code disk material with excellent magnetic properties. According to the actual application requirements of the magnetic code disk, the code disk material must have both moderate coercivity and high remanence to facilitate the writing (magnetization) and detection of magnetic pole signals. Sufficient remanence can ensure that the code disk has reliable output signal strength, and relatively high coercivity can ensure that the magnetic code disk has sufficient anti-electromagnetic interference capability under the premise of easy writing of magnetic poles.
[0004] FeCoCr-based alloy films with amplitude modulation decomposition characteristics are an important part of the permanent magnetic material family. Compared with many alloy materials such as SmCo, NdFeB, Fe(Co)Pt and CoCrTa, semi-hard magnetic FeCoCr-based alloy films have practical advantages such as good mechanical properties, no rare earth or precious metal elements, high Curie temperature (Tc is about 650℃), and easy magnetization. They are expected to be used as new magnetic encoding recording materials in future high-precision magnetic encoders. In addition, combined with the actual application requirements of magnetic code disk materials, the uniformity of magnetic code disk materials has an important influence on the accuracy of magnetic encoders and the stability of recorded magnetic signals. In order to ensure the anti-disturbance and read-write performance requirements of the magnetic pole signal recorded by the magnetic code disk, it is also necessary to solve the problem of uniformity and consistency of the microstructure.
[0005] Therefore, the improvement of the magnetic properties and uniformity control of FeCoCr magnetic code disk materials are of great significance to the development of high-precision magnetic encoders. How to improve the magnetic properties of FeCoCr thin film materials while taking into account the uniformity of the material on a small scale is a key issue that needs to be solved urgently. Summary of the invention
[0006] The present invention aims at the problem that it is difficult to improve the coercivity and remanence of the magnetic code disk thin film material FeCoCr at the same time, and at the same time ensure the uniformity of the magnetic code disk material, and proposes a method to greatly improve the coercivity and remanence of the FeCoCr film at the same time through material structure design, and ensure the uniformity of the material. Specifically, the technical solution of the present invention is as follows:
[0007] A method for preparing a high magnetic performance magnetic code disk FeCoCr material comprises the following steps:
[0008] (1) By magnetron sputtering, on the substrate, B target, FeCoCr target, B target and FeCoCr target were alternately sputtered in sequence, and then Ta layer was sputtered to obtain the prepared film; by constructing a two-periodic multilayer film structure of [B / FeCoCrMoTi]2, it is more conducive to the complete amplitude modulation decomposition of FeCoCr-based films, and the coercive force and remanence are greatly improved simultaneously. Specifically, after high-temperature annealing, B atoms preferentially combine with Cr atoms to form CrB2 phase, reducing the concentration of Cr atoms in the FeCo-rich phase, and even generating FeCo ferromagnetic phase in some areas, which can greatly improve the remanent magnetization intensity. The two-periodic structure can make B more fully combined with Cr.
[0009] Preferably, the FeCoCr target used in sputtering is a FeCoCrMoTi alloy target, and the nominal composition of the target is Fe: Co: Cr: Mo: Ti = 42: 25: 30: 3: 1 (wt%), and FeCoCrMoTi can be abbreviated as FeCoCr.
[0010] The background vacuum during sputtering is less than 3×10 -5 Pa, and the Ar gas partial pressure was maintained at 0.4 Pa.
[0011] (2) The prepared film is subjected to a graded annealing treatment.
[0012] Preferably, the vacuum degree of the graded annealing treatment is ≤5×10 -5 Pa, first anneal at 700-750℃ for 15-25min, then reduce the temperature to 600-650℃ for 25-35min. Graded annealing at two temperatures is beneficial to obtain high magnetic properties.
[0013] Preferably, the graded annealing is first performed at 700° C. for 20 min, and then the temperature is lowered to 630° C. for 30 min.
[0014] Preferably, the substrate material is selected from a silicon substrate or a non-magnetic stainless steel substrate.
[0015] Preferably, the reaction conditions for sputtering the B target are a sputtering power of 200 W and a sputtering time of 11 minutes and 6 seconds; the conditions for sputtering the FeCoCr target are a sputtering power of 100 W and a sputtering time of 27 minutes and 30 seconds; and the conditions for sputtering the Ta layer are a sputtering power of 50 W and a sputtering time of 5 minutes and 33 seconds.
[0016] The present invention also provides a high magnetic performance magnetic code disk FeCoCr material prepared by the method, comprising a substrate, a B layer, a FeCoCrMoTi layer and a protective layer, wherein the B layer has a thickness of 10-50nm and the FeCoCrMoTi layer has a thickness of 100nm.
[0017] Preferably, the thickness of the B layer is 20 nm, and the thickness of the FeCoCrMoTi layer is 100 nm.
[0018] Preferably, the FeCoCr material structure is: substrate / B / FeCoCrMoTi / B / FeCoCrMoTi / Ta.
[0019] Furthermore, the material of the present invention is applied to the field of magnetic code disks of high-precision magnetic encoders.
[0020] The beneficial effects brought by the technical solution of the present invention include at least:
[0021] The present invention can make the coercive force of the FeCoCr film reach 610 Oe and 5340 Oe respectively after introducing the 20nm B layer, which is 24.5% and 135.1% higher than that of the FeCoCrMoTi single-layer film, and can meet the actual application requirements of the magnetic encoder code disk. At the same time, the B atomic radius is small, and its diffusion behavior during the annealing process has little effect on the uniformity of the film microstructure.
[0022] According to thermodynamics and the difference in enthalpy changes of chemical reactions between B atoms and the three solvent atoms of Fe, Co, and Cr, B atoms preferentially combine with Cr atoms to form CrB2 phase, while repelling Co or Fe atoms, which is beneficial to further reduce the Cr content in the FeCo-rich phase. The concentration difference of Cr atoms in the Fe-Co-rich phase and the Cr-rich phase will also gradually increase, thereby promoting the further progress of spinodal decomposition. The experimental results show that the newly generated CrB2 phase in the wave film is closely related to the Fe-Co-rich phase. 0.7 Co 0.3 The unit cell volume of the phase is 23.45 Å 3 and 23.52 Å 3 , which is very close to the amplitude modulation decomposition phase, is conducive to improving the uniformity of the nanoscale microstructure. Therefore, the present invention improves the hard magnetic properties of the FeCoCr alloy film while achieving a more uniform microstructure, providing important scientific data support for its application in the field of high-density magnetic code disks, and has a lower cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 MH curves of FeCoCrMoTi films without B intercalation and with B intercalation, where (a) is a FeCoCrMoTi (200 nm) single-layer film sample; (b) is a multilayer film sample of B (20 nm) / FeCoCrMoTi (100 nm) / B (20 nm) / FeCoCrMoTi (100 nm).
[0025] Figure 2 (a) and (b) are the B 1s high-resolution XPS spectra of the single-layer film sample and the multilayer film sample obtained at different etching depths before and after the introduction of the B layer, respectively. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is described below in conjunction with the accompanying drawings.
[0027] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.
[0028] In the embodiments of the present invention, "image" and "picture" can sometimes be used interchangeably. It should be noted that when the difference between them is not emphasized, the meanings they want to express are the same. "of", "corresponding" and "corresponding" can sometimes be used interchangeably. It should be noted that when the difference between them is not emphasized, the meanings they want to express are the same.
[0029] In the embodiments of the present invention, sometimes a subscript such as W1 may be mistakenly written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are consistent.
[0030] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0031] Example 1
[0032] Step S1, providing a substrate layer and a FeCoCrMoTi alloy target, wherein the nominal composition of the target is Fe:Co:Cr:Mo:Ti = 42:25:30:3:1 (wt%); the substrate layer is a silicon substrate;
[0033] Step S2, by magnetron sputtering, on the substrate, alternately DC sputtering B target, FeCoCr target, B target and FeCoCr target in sequence, and then sputtering Ta layer, to obtain a prepared thin film; during the sputtering process, the background vacuum degree is less than 3×10 -5 Pa, Ar gas partial pressure was maintained at 0.4 Pa; the reaction conditions for sputtering B target were sputtering power 200W, sputtering rate 0.03 nm / s, and sputtering time 11 minutes and 6 seconds; the conditions for sputtering FeCoCr target were sputtering power 100W, sputtering rate 0.06 nm / s, and sputtering time 27 minutes and 30 seconds; the conditions for sputtering Ta layer were sputtering power 50W, sputtering rate 0.03 nm / s, and sputtering time 5 minutes and 33 seconds;
[0034] Step S3: anneal the prepared film at 700°C for 20 min, then lower the temperature to 630°C for 30 min. The vacuum degree of the annealing environment is better than 5×10 -5 Pa.
[0035] The structure of the FeCoCr thin film material of the magnetic code disk prepared in this embodiment is: substrate / B (20 nm) / FeCoCrMoTi (100 nm) / B (20 nm) / FeCoCrMoTi (100 nm) / Ta.
[0036] Comparative Example 1
[0037] The difference from Example 1 is that in step S2, the FeCoCr target is sputtered only once on the substrate, and the structure of the prepared magnetic code disk thin film material FeCoCr is: substrate / FeCoCrMoTi (100 nm) / Ta (10 nm).
[0038] Comparative Example 2
[0039] The difference from Example 1 is that in step S2, the B target and the FeCoCr target are sputtered on the substrate only once, and the structure of the prepared magnetic code disk thin film material FeCoCr is: substrate / B (20nm) / FeCoCrMoTi (100nm) / Ta (10nm).
[0040] The coercivity is about 400 Oe and the residual magnetization is 3000 Oe.
[0041] like Figure 1(a) and (b) are the MH curves of the FeCoCrMoTi film before and after the introduction of the B layer. It can be seen from the figure that the coercivity and remanence of the film are significantly improved after the introduction of the B layer. Specifically, before the introduction of the B layer, the in-plane coercivity of the FeCoCrMoTi single-layer film sample is 490 Oe, and the remanence is 185 emu / cm 3 (2325 Oe). When the B intercalation layer thickness is 20 nm, the in-plane coercivity, residual magnetization, and saturation magnetization all increase rapidly with the increase of the B layer thickness. When the B intercalation layer thickness is 20 nm, the coercivity reaches a maximum value of 610 Oe, and the residual magnetization is 435 emu / cm 3 (5466 Oe). Compared with FeCoCrMoTi single-layer film, the coercivity and remanence are increased by 24.5% and 135.1% respectively. At the same time, the material has the uniformity of nanoscale microstructure.
[0042] Figure 2 (a) and (b) are the B1s high-resolution XPS spectra of the FeCoCrMoTi single-layer film sample and the multilayer film sample obtained at different etching depths before and after the introduction of the B layer. This indicates that the CrB2 phase exists in the multilayer film sample of [B (20nm) / FeCoCrMoTi (100nm)]2.
[0043] In the single-layer film sample, as the spinodal decomposition process proceeds, the concentration difference of Cr atoms in the Fe-Co-rich phase and the Cr-rich phase gradually increases, and the gradient energy and strain energy also increase accordingly. When the concentration difference between the two phases reaches a certain value, the gradient energy and strain energy will hinder the further progress of spinodal decomposition. However, for the multilayer film sample after the introduction of B intercalation, B atoms tend to combine with Cr atoms to form CrB2 phase and repel Fe or Co atoms. This chemical energy overcomes the gradient energy and strain energy, expands the composition difference between the FeCo-rich phase and the Cr-rich phase, and causes the formation of Fe in some areas. 0.7 Co 0.3 The magnetic enhancement of the new phase effectively promotes the spinodal decomposition reaction. This leads to a significant increase in the residual magnetization. 0.7 Co 0.3 The main reason for the increase in coercivity is the increase in domain wall pinning caused by the formation of CrB2 phase and CrB2 phase) and the increase in phase composition difference. The present invention effectively promotes the amplitude modulation decomposition reaction by introducing chemical energy through doping B element to overcome gradient energy and strain energy, and opens up a new feasible path for the simultaneous optimization of coercivity and residual magnetic properties of FeCoCr semi-hard magnetic alloy. In addition, by utilizing the small radius of B atoms, the influence on the uniformity of the film microstructure is minimized as much as possible, which is conducive to improving the uniformity of nanoscale microstructure. The present invention improves the magnetic properties of the film while taking into account the uniformity of the material, providing an important scientific basis for the preparation and application of new high-performance magnetic code disks.
[0044] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a FeCoCr material for a magnetic code disk with high magnetic performance, characterized in that: The following steps are involved: (1) By magnetron sputtering, on the substrate, the B target, FeCoCr target, B target and FeCoCr target were alternately sputtered by direct current, and then the Ta layer was sputtered to obtain the prepared thin film; the background vacuum degree during the sputtering process was less than 3×10 -5 Pa, Ar gas partial pressure was maintained at 0.4 Pa; (2) The prepared film is subjected to a graded annealing treatment.
2. The method according to claim 1, characterized in that The FeCoCr target used in sputtering is a FeCoCrMoTi alloy target, and the nominal composition of the target is Fe:Co:Cr:Mo:Ti = 42:25:30:3:
1.
3. The method according to claim 1, characterized in that: The vacuum degree of graded annealing treatment is ≤5×10 -5 Pa, first anneal at 700-750℃ for 15-25min, then reduce the temperature to 600-650℃ for 25-35min.
4. The method according to claim 3, characterized in that The graded annealing was first performed at 700 °C for 20 min, and then the temperature was lowered to 630 °C for 30 min.
5. The method according to claim 1, characterized in that The substrate material is selected from a silicon substrate or a non-magnetic stainless steel substrate.
6. The method according to claim 1, characterized in that The reaction conditions for sputtering the B target were a sputtering power of 200 W and a sputtering time of 11 minutes and 6 seconds; the conditions for sputtering the FeCoCr target were a sputtering power of 100 W and a sputtering time of 27 minutes and 30 seconds; and the conditions for sputtering the Ta layer were a sputtering power of 50 W and a sputtering time of 5 minutes and 33 seconds.
7. The high magnetic performance magnetic code disk FeCoCr material prepared by the method according to any one of claims 1 to 6, characterized in that: It comprises a substrate, a B layer, a FeCoCrMoTi layer and a protective layer, wherein the B layer has a thickness of 10-50 nm, and the FeCoCrMoTi layer has a thickness of 100 nm.
8. The FeCoCr material according to claim 7, characterized in that The thickness of the B layer is 20 nm, and the thickness of the FeCoCrMoTi layer is 100 nm.
9. The FeCoCr material according to claim 7, characterized in that: The FeCoCr material structure is: substrate / B / FeCoCrMoTi / B / FeCoCrMoTi / Ta.
10. Use of the FeCoCr material prepared by the method according to any one of claims 1 to 6 or the FeCoCr material according to any one of claims 7 to 9 in the field of magnetic code disks of high-precision magnetic encoders.
Citation Information
Patent Citations
Magnetic recording medium and its fabrication method
CN1070278A
Component gradient magnetic metal-magnetic oxide particle film and preparation method thereof
CN112927881A
FeCoCr magnetic code disc thin film material and preparation method thereof
CN114086136A
FeCoCr magnetic code disc thin film material and preparation method and application thereof
CN114606471A
High-magnetic-performance FeGaB magnetoelectric film and preparation method thereof
CN115612988A
Cited By
FeCoCr / Al magnetic code disc material and preparation method and application thereof
CN120575126A
